Intraseasonal descriptors and extremes in South African rainfall. Part II : Summer teleconnections across multiple timescales - (:unkn) unknown (My University, 2023)
Extreme events contribute significantly to rainfall variability in semi-arid regions like South Africa. Here, following the definition of a novel typology of rainfall extremes, disentangling large- and small-scale events in Part I, we use quality-controlled observational databases in South Africa, the ERA5 reanalysis and satellite estimates TRMM-3B42 to examine the relationship between these two types of rainfall extremes and different modes of climate variability at various timescales. At low frequencies, rainfall extremes are assessed at interannual (IV: 2–8 years) and quasi-decadal (QDV: 8–13 years) timescales, which are primarily associated with the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), respectively. At subseasonal timescales, the typology of rainfall extremes is analysed depending on the synoptic configurations, as inferred by seven convective regimes including tropical temperate troughs (TTTs: 3–7 days), and the intraseasonal variability associated with the Madden–Julien Oscillation (MJO: 30–60 days). At the IV timescale, the occurrence of large-scale extremes is substantially higher during its wet phases thereby suggesting a 400% rise in the occurrence of large-scale extremes as compared to its dry phases. At the QDV timescale, variability mostly relates to the modulation of small-scale extremes during its wet phases. Teleconnections with global sea surface temperature (SST) confirm that La Niña conditions favour overall wet conditions and extremes in South Africa. The numbers of large-scale extremes are consistently related to warmer SSTs in the North Atlantic, while their link with warmer Indian and tropical South Atlantic oceans is found to be statistically independent of the state of ENSO. At the subseasonal timescales, large-scale extremes largely occur during three out of the seven convective regimes identified in the southern African region whereas small-scale extremes ar
Keywords: African Research